BUNGLON DALAM KARYA SENI GRAFIS - ADITYA YULIANTONI, Dr. Budiwirman, M.Pd., Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2018)
The creation of this final graphic work aims to visualize the camouflage of chameleons possessed by humans. The authors expose darkside of human trait that utilizes the surrounding environment for its own satisfaction.This final work started with, preparation stage, elaboration, synthesis, concept realization and completion stage. In this final work the author brings up the style in the work. The style that writers apply in this final paper is Cubism style. In the final work that the author makes many displays of rectangular objects that the author stacked scattered. And highlight the main object of chameleon animals.Through this graphic art, writers is developed a form of artwork. Some works of art that have been exclusively presented are, 1) “berburu”, 2) “suap”, 3) “korupsi”, 4) “pengemis kaya”, 5) “serakah”, 6) “seharusnya”, 7) “berlawanan”, 8) “tipu muslihat”, 9) “uang”, 10) “harta, tahta dan wanita”. This is the camouflage nature of chameleons in humans. .Keywords: Chameleon, (serigraphy) type of cliches broken.